2017
DOI: 10.1016/j.atmosenv.2017.09.028
|View full text |Cite
|
Sign up to set email alerts
|

The influence of roadside solid and vegetation barriers on near-road air quality

Abstract: h i g h l i g h t s The Influence of roadside barriers on the near-road air quality was investigated. RANS technique coupled with the k À ε realizable turbulence model was utilized. Vegetation barrier depending on LAD can improve or deteriorate the air quality. The dense canopy can improve the near-road air quality by inducing vertical mixing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 55 publications
(61 reference statements)
1
24
0
Order By: Relevance
“…within and beyond the barrier) 34,53 . Conversely, very low-porosity vegetation can limit pollution removal by restricting infiltration and forcing air pollutants to flow above and around the barrier or to recirculate and accumulate on the upwind or source side 29,54 . An optimal porosity may therefore be inferred to exist between both extremes.…”
Section: Local Scalementioning
confidence: 99%
See 4 more Smart Citations
“…within and beyond the barrier) 34,53 . Conversely, very low-porosity vegetation can limit pollution removal by restricting infiltration and forcing air pollutants to flow above and around the barrier or to recirculate and accumulate on the upwind or source side 29,54 . An optimal porosity may therefore be inferred to exist between both extremes.…”
Section: Local Scalementioning
confidence: 99%
“…A higher vegetation barrier density generally results in lower downwind concentrations of both PM 86,98,99 and gaseous pollutants 54,100 . However, CFD modelling undertaken by Ghasemian et al 54 found that a LAD of 3.33 m 2 /m 3 reduced downwind concentrations of roadway emissions (represented by a tracer gas) by 10%, whereas a LAD of 1 m 2 /m 3 increased downwind concentrations by 15%.…”
Section: Density and Porositymentioning
confidence: 99%
See 3 more Smart Citations